Sum operator methods for the existence and uniqueness of solution to infinite-point boundary value problems for fractional differential equations. Issue 3 (2018) - Wang, Yupin; Sun, Shurong
In this paper, we study infinite-point boundary value problems for a class of higher-order nonlinear factional differential equations involving the Riemann-Liouville derivative. By using sum operator methods, the existence and uniqueness of solution to this kind of problems is obtained and iterative sequence of the positive solution is structured. Two examples are provided for our new results.